PENGEMBANGAN MEDIA RUBIK CARD TEMATIK SUBTEMA SUMBER ENERGI KELAS IV SEKOLAH DASAR - Lusianti Eka Kurnia; Henry Januar Saputra; Khusnul Fajriyah (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2020)
The purpose of this study was to determine student responses after using the learning media developed, namely the Thematic Rubik Card. The trial was carried out on class IVB Khodijah and IVC Abdurrahman students at SDIT Permata Bunda Mranggen Demak. The research method used is development research. The final stage in this research is that the researcher uses a student response questionnaire in collecting data. The questionnaire is in the form of 14 questions about learning that has been carried out using the Thematic Rubik Card media. The results of the student response questionnaire analysis in class IVB Khodijah showed a percentage of 97.02% and in class IVC Abdurrahman showed a percentage of 94.40%, meaning that Thematic Rubik Card media can be an alternative learning media that is very feasible to be applied to learning Theme 2 Always Save Energy , Sub-theme 1 Sources of Energy in grade IV SD to arouse students' interest and desire in learning.